Accuracy of rapid diagnosis of Talaromyces marneffei: A systematic review and meta-analysis. - Chuanyi Ning; Jingzhen Lai; Wudi Wei; Bo Zhou; Jiegang Huang; Junjun Jiang; Bingyu Liang; Yanyan Liao; Ning Zang; Cunwei Cao; Hui Chen; Li Ye; et al. (PLoS ONE, 2018)
Background To examine the accuracy of Rapid Diagnosis of Talaromyces marneffei (RDTM) in order to improve diagnosis and treatment for clinical measures and reduce the mortality due to associated infections. Methods In this systematic review and meta-analysis, we screened PubMed, Ovid (Cochrane library) and Web of Science, Chinese database CNKI and Wanfang for articles published between 1956 and December, 2017. Data were taken from cross-sectional studies as well as from baseline measurements in longitudinal studies with clinical follow-up. Articles were excluded if they did not contain a cohort with T. marneffei and a control cohort or a cohort with standard fungus culture. Data were extracted by two authors and checked by three for accuracy. For quality assessment, modified QUADAS-2 criteria were used. Results The 26 included diagnostic studies enrolled 5,594 objectives in 632 patients with T. marneffei infections and 2,612 negative controls between 1996 and 2017 in Thailand, Vietnam and China. The total combined sensitivity and specificity of rapid diagnosis of T. marneffei was 0.82 (95% CI: 0.68-0.90) and 0.99 (95% CI: 0.98-1.00). According to the experimental method, the included studies can be divided into three subgroups, including PCR-based, ELISA-based and others. The results showed these three subgroups had a highly pooled specificity of 1.00 (95% CI: 0.99-1.00), 0.99 (0.98-1.00) and 0.97 (95% CI: 0.91-1.00), respectively, while combined sensitivity was 0.84 (95% CI: 0.37-0.98), 0.82 (95% CI: 0.64-0.92) and 0.77 (95% CI: 0.54-0.91), respectively. Conclusions Although serological methods with a high specificity is essential for potential rapid diagnostic, false-negative results can be obtained in the serum samples, there is no suitable rapid serological test to refer to as is the case with TM infection.